Effect of protein and energy levels in sweet sorghum bagasse leaf residue-based diets on the performance of growing Deccani lambs - Yerradoddi, R.R.; Khan, A.A.; Mallampalli, S.R.; Devulapalli, R.; Kodukula, P.; Blümmel, Michael (Springer, 2015)
Sweet sorghum bagasse with leaf residue (SSBLR) based complete diets with high or low protein and high- or low-energy levels were evaluated in a 60-day growth trial using growing sheep. Twenty-eight Deccani ram lambs were divided into four groups (16.0 ± 0.59 kg) of seven each and fed low-protein high-/low-energy and high-protein high-/low-energy diets ad lib. Average daily gain (g; P < 0.05) and feed efficiency (P < 0.01) were significantly higher in lambs fed high energy than those with low-energy diets, and cost per kg gain ($) was significantly lower (P < 0.05) in low protein than high-protein diets. Dry matter intake (DMI) (g/day) was not significantly affected either by protein or energy level in the diet, but dry matter (DM), organic matter (OM), protein, and neutral detergent fiber (NDF) digestibilities were higher significantly (P < 0.01) in high protein/energy diets than low protein/energy diets. Crude protein (CP) intake (g/day) was significantly (P < 0.001) higher in lambs fed high protein than low-protein diets. However, N balance (g/day) was significantly (P < 0.001) higher in lambs fed low protein than high-protein diets. It is concluded that feeding of SSBLR-based diet with low protein (CP 12.9 %) and high energy (9.4 MJ metabolizable energy (ME)/kg DM) was recommended for better performance, nitrogen retention, and returns from growing Deccani ram lambs.